Against Paretianism: A Wealth Creation Approach to Business Ethics. Issue 3 (4th July 2022) - Young, Carson
Abstract : How should we distinguish between ethical and unethical ways of pursuing profit in a market? The market failures approach (MFA) to business ethics purports to provide an answer to this question. I argue that it fails to do so. The source of this failure is the MFA's reliance on Pareto efficiency as a core ethical principle. Many ethically "preferred" tactics for seeking profit cannot be justified by appeal to Pareto efficiency. One important reason for this is that Pareto efficiency, as understood by the theory of welfare economics upon which the MFA relies, assumes a static conception of efficiency. This is a problem because many ethically "preferred" tactics can only be justified by appeal to dynamic efficiency considerations. I argue that, instead of Pareto efficiency, we should look to the value of wealth creation to understand the ethical constraints on how market actors may pursue profit.